The policy entrepreneurs and community participation in the establishment of marine conservation in Sabah: case study of Tun Mustapha Park (TMP) / Erica Joanne Reuben - Reuben, Erica Joanne (2022)
The focus of the research is to study the role of policy entrepreneurs in the establishment of Tun Mustapha Park (TMP). The research is significant in understanding the importance of the roles played by the policy entrepreneur in the process of establishing TMP. Meanwhile, the objectives of this research are to study the strategies, methods and tools as well as the most effective strategies, methods and tools used by the policy entrepreneurs namely Sabah Park, WWF-Malaysia and Sabah Fisheries Department (DOFM) to encourage local community’s support in the establishment of Tun Mustapha Park. This case study was guided by the participatory theory, research question and research objectives. In this study, the researcher conducted interviews to collect primary data from the relevant interviewees selected using purposive and snowball sampling method. The interviewees of this study are the staffs of Sabah Parks, WWF-Malaysia, Sabah Fisheries Department (DOFM), the TMP’s community members and leaders. In addition, the secondary data of this study were gathered from journal articles. The gathered data were analyzed using thematic analysis. The six strategies, methods and tools used by the policy entrepreneurs but the most effective strategies were to strengthen community’s inclusion in socio-economic and to establish community’s empowerment in developing TMP zoning mapping and enforcement